Factors Influencing Job Retention of Professional Nurses in Community Hospitals at Nakhon Sawan Province - Harnpun, Pongthawat; Ngammeesri , Luksamee (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
This objectives of this research were to: 1) assess the level of job retention among professional nurses in community hospitals at Nakhon Sawan Province, and 2) identify factors influencing their retention. The study sample comprised 208 full-time professional nurses who were not in leadership roles, specifically excluding those serving as heads of workgroups, in community hospitals within Nakhon Sawan Province. Data collection tools included a questionnaire with a content validity index ranging from 0.67 to 1.00 and a reliability coefficient of 0.947. Statistical methods employed included mean, standard deviation, and multiple regression analysis. The research findings were as follows: 1. The overall level of job retention among professional nurses in community hospitals at Nakhon Sawan Province was ad a high level ( = 3.74, S.D. = 0.75). Among the factors examined, job characteristics received the highest mean score ( = 4.06, S.D. = 0.52), followed by personal characteristics ( = 3.99, S.D. = 0.49), manager characteristics ( = 3.95, S.D. = 0.75), and organizational characteristics ( = 3.58, S.D. = 0.66). All these factors were rated at a high level. 2. Factors affecting influencing job retention among professional nurses included personal characteristics, organizational characteristics, and task requirements. These factors collectively predicted job retention at 64.7% (R2 = 0.647) and with statistically significant at the 0.05 level. However, manager characteristics did not have significantly impact on job retention.